ORION: A simulation environment for spacecraft formation flight, capture, and orbital robotics - Wilde, Markus; Kaplinger, Brian; Tiauw Go; Gutierrez, Hector; Kirk, Daniel (2016 IEEE Aerospace Conference, 2016)
The Florida Institute of Technology developed the Orbital Robotic Interaction, On-orbit servicing, and Navigation (ORION) laboratory for the testing of spacecraft guidance, navigation, and control systems for spacecraft proximity maneuvers, and autonomous or telerobotic capture. ORION combines the precise kinematics simulation and large load-bearing capacity of a Cartesian robotic system with the vehicle dynamics simulation capabilities of an air-bearing flat-floor setup, with all vehicles in the simulation being tracked by an optical tracking system. The vehicles can simulate the kinematics and dynamics aspects of three-dimensional formation flight, final approach of uncooperative target objects, and capture. In addition to spacecraft maneuvers, ORION will also serve experiments and tests in the domains of unmanned aerial vehicles and terrestrial robots. This paper describes the design and capabilities of the six degrees of freedom maneuver kinematics simulator of the ORION lab, and the six degrees of freedom air-bearing vehicles for the flat-floor. Furthermore, the paper provides examples of the ongoing research activities: the development and test of capture tools for space debris objects, the project Assessment, Diagnostics, Corrections and Ground Testing of RINGS (Resonant Inductive Near-field Generation Systems), and the development and validation of a distributed virtual sensor for deflection, rate of rotation and acceleration of flexible structures based on fiber Bragg sensor arrays.